RELAWAN POLITIK DALAM SIRKULASI ELITE POLITIK DI INDONESIA PASCA-ORDE BARU - Cleorisa Cheguevara Riswan; Rahardian Putra Setia Budi; Kamaruddin Salim (Jurnal GeoCivic, 2024)
The focus of this research is related to political volunteers in the circulation of post-Orba political elites. Political volunteers are individuals who have institutionalized themselves in interest groups who play as an active role in political activities, both independently and in an organized manner. The involvement of political volunteers in the circulation of power elites in Indonesia marked the change from New Order politics to the Reform Order. As Vilfredo Pareto said, the circulation of elites in power is the process of replacing political leadership in a country or government. The results of this research portray that political volunteers have developed into important actors in political contestation and are able to influence the course of Indonesian political dynamics. Those factors of involving political volunteers include social change, advances in information technology, and shifts in political culture. The strength of political volunteers as a shadow party actually has several important points, first, having a flexible and broad social network. Second, become an influencer who is able to determine and control young and independent people. Third, groups are free to determine political attitudes. Fourth, political volunteers become a balancing group for the power of the bureaucracy and political parties. Fifth, the volunteer group comes from a generation that is literate in information technology, which then becomes the basis of their power in politics.